Process optimization of mung bean (Vigna radiata) starch extraction - Samaniego, Khris P.; Gonzales, Benjamin A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
Mung bean starch extraction was optimized using face-centered central composite design Response Surface Methodology (RSM) with steeping time (A, 8-24h) and NaOH (B, 0.01-1.0N) concentration as factors, and moisture content and solubility as responses. The resulting equations for moisture content and solubility are shown below: 𝑀𝑜𝑖𝑠𝑡𝑢𝑟𝑒 𝑐𝑜𝑛𝑡𝑒𝑛𝑡 (%) = −9.76581 + 3.17985 ∗ 𝐴 − 0.098026 ∗ 𝐴2 𝑆𝑜𝑙𝑢𝑏𝑖𝑙𝑖𝑡𝑦 (%) = 9.40069 − 24.00723 ∗ 𝐵 + 27.77986𝐵2. All actual responses from model validation were within the prediction and confidence intervals, however, these intervals were wide, including points which might pose microbiological risk. This indicates a valid but unreliable model. One sample t-test showed that actual responses were not significantly different from predicted responses, except for one non optimal run. Optimal processing conditions can be selected at any steeping time and NaOH concentration combinations ranging from 8 to 24 hours, and 0.01 to 0.06N NaOH, to attain minimum moisture and solubility with minimal alkaline concentration. Mung bean starch extracted from the optimal run was characterized for moisture (11.2 ± 0.06%), ash (0.48 ± 0.01%), protein (3.08 ±0.01%) and fat (0.29 ± 0.06%). The starch was found to have a solubility of 7.42 ± 1.08% and swelling power of 6.75 ± 0.06%. Shape of granules varied from round to oval, with long axis diameters ranging from 11.30 - 35.96 μm and short axis diameter of 8.67 - 22.75 μm. To yield better optimization models, it is recommended to look at responses related to starch purity such as protein and ash content and verify these with characterization results.
Thesis Classification: F
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Mung bean -- Processing